Advancing collaborative management in Bukit Rimbang Baling Wildlife Reserve, Riau, Indonesia - Wijayanto Agustinus; Wibowo Prianto; Sudarno Nano; Wilianto Erwin; Cahyono Topan; Ario Digdo Akbar; Holisudin Ujang; Hansen Siregar Andri (BIO Web of Conferences)
Collaborative management (CM) in protected areas refers to a system in which multiple stakeholders actively participate in managing protected areas (PAs). The collaboration can take various forms, ranging from government-led to community-based approaches. Bukit Rimbang Bukit Baling Wildlife Reserve (BRBB WR), Central Sumatra is known as a long-term priority Sumatran tiger (Panthera tigris sumatrae) landscape globally. At the same time, the local and traditional communities have been inhabiting the area for hundreds of years and generally have livelihoods that are closely related to the nearby natural resources, including rubber products and other natural resources. This study examines the challenges of managing BRBB WR, identifying the gap, and exploring collaborative strategies to balance conservation and sustainable livelihoods. The study employs a descriptive analysis approach using interviews, focus group discussions, and direct field observations. Findings highlight key challenges, including illegal activities within the reserve, limited community awareness of regulations, restricted management capacity, and a lack of inclusive collaborative planning. Strengthening CM strategies requires enhancing leadership capacity, establishing inclusive partnerships with key stakeholders, and implementing joint monitoring and evaluation frameworks. These efforts are essential for ensuring effective conservation while supporting the well-being of local communities within BRBB WR.